2021
DOI: 10.6007/ijarbss/v11-i11/11683
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Openness and Connectedness During Online Learning

Abstract: Covid-19 pandemic has accelerated the need for open and distance learning (ODL). Past studies investigate the perception of ODL based on learner-to-learner engagement, leanerto-instructor engagement and learner-to-content engagement. Nevertheless, lack of study conducted to explore ways to boost students' motivation during ODL. This study is necessary to investigate strategies to boost students' motivation during ODL. By exploring the openness and connectedness of the students during ODL, it gives significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Haythornthwaite et al (2000) stated that close contact between students is important during online learning to avoid feeling isolated and dropped out. The findings for Learner-to-Content Interaction are supported by Tahir et al (2021) in their study that connectedness is demonstrated in ODL through student engagement and content. Activities can improve students' understanding of the subject and getting an overview of the content is important before the class starts (Zanne et al, 2022).…”
Section: Conclusion Summary Of Findings and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, Haythornthwaite et al (2000) stated that close contact between students is important during online learning to avoid feeling isolated and dropped out. The findings for Learner-to-Content Interaction are supported by Tahir et al (2021) in their study that connectedness is demonstrated in ODL through student engagement and content. Activities can improve students' understanding of the subject and getting an overview of the content is important before the class starts (Zanne et al, 2022).…”
Section: Conclusion Summary Of Findings and Discussionmentioning
confidence: 64%
“…This is further emphasized with the paired samples t-test where the students are more in agreement on the application of Telegram for Learner-to-Instructor interactions. On the other hand, while claiming that students feel a prominent level of openness during ODL shown by student-to-student engagement as well as student-teacher engagement, Tahir et al (2021) found peer involvement as a key factor in increasing openness and being motivated during ODL sessions. Additionally, Haythornthwaite et al (2000) stated that close contact between students is important during online learning to avoid feeling isolated and dropped out.…”
Section: Conclusion Summary Of Findings and Discussionmentioning
confidence: 92%